DESENTRALISASI FISKAL DAN PERUBAHAN STRUKTUR EKONOMI: STUDI PERBANDINGAN KAWASAN SULAWESI DAN JAWA - Muh. Amir Arham (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2014)
Fiscal decentralization policies by giving greater authority to the regions to create efficiency and effectiveness to provide public goods, because the area is considered better understand the preferences of the community. Besides, fiscal decentralization policies can accelerate economic growth and changes in economic structure that has a devastating impact on the region is still considered backward. In general, backward areas still rely on primary sectors such districts/municipalities in Sulawesi, while the districts/municipalities in Java, relying on non-primary sector tends to be more advanced. Therefore, in general the economy is still underdeveloped Sulawesi compared to Java. The purpose of this research is to analyze the effect of fiscal decentralization on economic structural change districts/municipalities by comparing the two areas considered different economic structure, Sulawesi and Java. By using a panel analysis of data from 2001-2010 results showed that the fiscal decentralization policies has no effect on changes in the economic structure in Sulawesi. Java, while in the region shows that the negative effect of fiscal decentralization, it means diminishing the role of the primary sector, which leads to changes in the economic structure.